Engineering Properties of Fresh Pea Kernels (Pisum sativum L.) - Kumar, Mukesh; Arora, Sadhna; Sharma, Satish (Journal of Agricultural Engineering, 2004)
A study was conducted to determine physical, frictional, and flow properties of different varieties of pea (Pisum sativum L.) Physical frictional and flow properties of 'Arkel','Ageti', 'Pb-87','Pb-88' and 'Mithi phali' varieties were determined. There were no significant differences in particle density and porosity for different varities. However, all other properties has significant differences. Flow properties were observed to be linearly dependent upon compaction load.